Width of phonon sidebands in the Brownian oscillator model - Ye, Jun (2011)
The line width dependence of zero-phonon lines and phonon sidebands on temperature, bath dissipation, and electron−phonon coupling is studied for an underdamped Brownian oscillator model with an Ohmic dissipative bath. Factors determining the line widths vary from the zero-phonon lines to the phonon sidebands. The control-parameter space of line broadening has been mapped out, revealing that the line widths of the zero-phonon lines and phonon sidebands are linearly dependent on both the temperature and the Huang−Rhys factor. It is also found that the dependence of the line widths on the bath damping factor is linear for the zero-phonon lines and quadratic for the phonon sidebands.